Copyright reversion : reclaiming lost culture and getting authors paid / Joshua Yuvaraj, University of Auckland, Rebecca Giblin, Melbourne Law School. - Yuvaraj, Joshua; Giblin, Rebecca (Cambridge intellectual property and information law., 2025)
Copyright is meant to promote access to knowledge and culture and reward creators. But around the world, publishers, record labels and other investors continue to hoover up the rights and rewards due to creators and leave masses of creativity locked away from the public. This book shows why this bargain is broken, and how reverting copyright to creators can help redress it - allowing them to revitalise old works, turbocharged by technological advances that are providing more opportunities to do so than ever before. With cutting-edge empirical and doctrinal analysis of dominant reversion models from the United States, the Commonwealth and the EU, the book provides policymakers and academics with best-practice principles for designing reversion mechanisms that can help copyright laws do a better job of supporting the public interest in access while helping artists get paid. This title is also available as open access on Cambridge Core.